2009
DOI: 10.1111/j.1741-1130.2009.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Care and Service Trajectories for People With Intellectual Disabilities: Defining Its Course and Quality Determinants From the Client's Perspective

Abstract: Care and service trajectories are identifiable routes through service systems that consist of all steps that people with intellectual disabilities (ID) and their families have to take to realize the care and services they need. Trajectories are especially prominent during the transitions from children's services to adult services. Within a service system in Noord-Brabant (in the Netherlands), the authors examined the course of such trajectories and their main bottlenecks and sought to identify their quality de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 37 publications
0
43
0
6
Order By: Relevance
“…These models include family-centered care (Gabovitch and Curtin 2009), case management (Parellada et al 2013), or community mental health services (Brookman-Frazee et al 2011). Along this line, Barelds et al examined the quality of ID services in the Netherlands from users' and parents' point of view and in the context of integrated care (Barelds et al 2009(Barelds et al , 2010. This team defined integrated care as a model for the delivery of continuous and holistic care, as well as the techniques and processes involved in achieving this goal.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…These models include family-centered care (Gabovitch and Curtin 2009), case management (Parellada et al 2013), or community mental health services (Brookman-Frazee et al 2011). Along this line, Barelds et al examined the quality of ID services in the Netherlands from users' and parents' point of view and in the context of integrated care (Barelds et al 2009(Barelds et al , 2010. This team defined integrated care as a model for the delivery of continuous and holistic care, as well as the techniques and processes involved in achieving this goal.…”
Section: Introductionmentioning
confidence: 98%
“…Barelds et al (2009) found that persons with intellectual disabilities (ID) and their families' perception of the quality of services depended on the obstacles they encountered along their service trajectory. Another study (Little 2003) showed that early access to services is positively associated with parental perceptions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations